Greenhouse control and monitoring system - Yeap, Sim Keat (2019)
In modern days, people started to use modern technology in their daily life and in many sector to minimize their work and maximize their production. There are various kinds of systems that are being implemented in agriculture sector. In this project, a system will be developed to monitor and control the greenhouse temperature. The temperature of the greenhouse that used this system will be monitored and controlled remotely. User will receive an emergency notification to their cell phone when the surrounding temperature is unusual. It can be said that user did not have to hire a worker to stay at the greenhouse to monitor it. Thus, this project aims to study existing greenhouse system and develop a new greenhouse system which provides an affordable temperature monitoring and control greenhouse system. Rapid Application Development (RAD) is chosen as the methodology used to develop this system. The RAD methodology involves four main stages which include requirement planning, user design, construction and cutover.